TOXIC EFFECTS OF PHORATE ON BLOOD CELL PROFILES OF COMMON CARP Cyprinus carpio ON EXPOSURE TO LETHAL AND SUBLETHAL CONCENTRATIONS - DR. G. LAKSHMAIAH (International Journal of Pharma and Bio Sciences, 2014)
Phorate is an organophosphorus insecticide and miticide which is widely used throughout the world and also in India and Andhra Pradesh as a broad-spectrum insecticide for numerous crops. Fingerlings of Cyprinus carpio were exposed to acute lethal toxicity of Phorate for one day and 4 days and chronic sublethal toxicity of Phorate for 1, 7, 15 and 30 days. Blood cell profiles like red blood cell (RBC) and white blood cell (WBC) counts were studied in the fish exposed to acute and chronic toxicity of Phorate. Significant alterations were observed in the blood cell profiles of both acute and chronic toxicity exposed fish. The present study enhanced the knowledge of haematological alterations in fish due to acute lethal and chronic sublethal exposure of Phorate.